2009
DOI: 10.1016/j.virol.2009.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the 2-5OAS/RNase L pathway in CVB1 or HAV/18f infected FRhK-4 cells does not require induction of OAS1 or OAS2 expression

Abstract: The latent, constitutively expressed protein RNase L is activated in coxsackievirus and HAV strain 18f infected FRhK-4 cells. Endogenous oligoadenylate synthetase (OAS) from uninfected and virus infected cell extracts synthesizes active forms of the triphosphorylated 2-5A oligomer (the only known activator of RNase L) in vitro and endogenous 2-5A is detected in infected cell extracts. However, only the largest OAS isoform, OAS3, is readily detected throughout the time course of infection. While IFNbeta treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…The activation of RNase L without the further induction of OAS expression, as we have shown in JFH‐1 replicon cells, is not unique to HCV. It was reported that in the coxsackievirus or hepatitis A virus infection of monkey kidney FRhK‐4 cells, RNase L could be activated with no apparent induction of the OAS1 or OAS2 proteins; in these FRhK‐4 experiments, OAS3 was constitutively expressed at a relatively high level, and this expression level remained unchanged throughout the infection [31]. It appears likely that only a small quantity of OAS protein is needed as a catalytic enzyme for the activation of RNase L. Thus, constitutively expressed OAS1 and/or OAS3 might play a safeguard role through the activation of RNase L in the early stage of antiviral response against HCV infection.…”
Section: Discussionmentioning
confidence: 88%
“…The activation of RNase L without the further induction of OAS expression, as we have shown in JFH‐1 replicon cells, is not unique to HCV. It was reported that in the coxsackievirus or hepatitis A virus infection of monkey kidney FRhK‐4 cells, RNase L could be activated with no apparent induction of the OAS1 or OAS2 proteins; in these FRhK‐4 experiments, OAS3 was constitutively expressed at a relatively high level, and this expression level remained unchanged throughout the infection [31]. It appears likely that only a small quantity of OAS protein is needed as a catalytic enzyme for the activation of RNase L. Thus, constitutively expressed OAS1 and/or OAS3 might play a safeguard role through the activation of RNase L in the early stage of antiviral response against HCV infection.…”
Section: Discussionmentioning
confidence: 88%
“…Kulka and others () demonstrated that HAV‐infected FRhK‐4 cells activate the 2’‐5'oligoadenylate synthetase/RNase L pathway. Activated RNase L degrades viral RNA and cellular single‐stranded RNA.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptive immune response seems to be sufficient despite the interference of HAV proteins with the innate immune response, e.g. IRF-3 [7,12,14] to clear the virus. Increased age is related to an increased HAV morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%